2016
DOI: 10.3141/2560-12
|View full text |Cite
|
Sign up to set email alerts
|

New Extended Discrete First-Order Model to Reproduce Propagation of Jam Waves

Abstract: In this paper we propose an extension of the discrete LWR model of the cell-transmission model type, to reproduce the capacity drop and the propagation of jam waves. Recently studies have tried to incorporate the capacity drop into discrete first-order traffic flow models for traffic optimization purpose. It is found that the inflow to a discharging cell predicted by these models might have been overestimated, which will influence the propagation of a jam wave. Empirical analysis has been carried out to confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…In order to maintain the simplicity of the model, extensions with linear formulations were considered for use in our model. Han et al (2016) provided an extension of first order model with a linear formulation in order to incorporate the capacity drop phenomena by modifying the supply function of the downstream cell in order to reflect the reduced flow discharge during congestion. This was an extension of a similar method employed by Roncoli, Papageorgiou, and Papamichail (2015) where the demand function is linearly modified instead of the supply function.…”
Section: Capacity Dropmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to maintain the simplicity of the model, extensions with linear formulations were considered for use in our model. Han et al (2016) provided an extension of first order model with a linear formulation in order to incorporate the capacity drop phenomena by modifying the supply function of the downstream cell in order to reflect the reduced flow discharge during congestion. This was an extension of a similar method employed by Roncoli, Papageorgiou, and Papamichail (2015) where the demand function is linearly modified instead of the supply function.…”
Section: Capacity Dropmentioning
confidence: 99%
“…This was an extension of a similar method employed by Roncoli, Papageorgiou, and Papamichail (2015) where the demand function is linearly modified instead of the supply function. The approach used by Han et al (2016) is used to incorporate CD in the model. The formulation is described in brief here.…”
Section: Capacity Dropmentioning
confidence: 99%
“…It is found that the type of traffic jam considered by most of the above mentioned models is only the standing queue. In (Han et al, 2016), it has been tested that most of the above mentioned models can not reproduce the propagation of jam waves accurately. Thus, we have proposed a new extension of the discrete first-order model to reproduce the propagation of jam waves more accurately, which will be briefly introduced in the next section.…”
Section: Extended Versions Of the Ctmmentioning
confidence: 99%
“…As has been discussed in (Han et al, 2016), the cell-transmission model and many of its variants have difficulties in reproducing the propagation of jam waves accurately. One reason is that capacity drop has not been adequately incorporated.…”
Section: The New Extended Ctmmentioning
confidence: 99%
See 1 more Smart Citation